2020
DOI: 10.1016/j.ajpath.2019.10.019
|View full text |Cite|
|
Sign up to set email alerts
|

p53-Regulated Long Noncoding RNA PRECSIT Promotes Progression of Cutaneous Squamous Cell Carcinoma via STAT3 Signaling

Abstract: Long noncoding RNAs (lncRNAs) have emerged as putative biomarkers and therapeutic targets in cancer. The role of lncRNA LINC00346 in cutaneous squamous carcinoma (cSCC) was examined. The expression of LINC00346 was up-regulated in cSCC cells compared with normal human epidermal keratinocytes. Elevated expression of LINC00346 was noted in tumor cells in cSCC tissue sections in vivo, as compared with cSCC in situ, and actinic keratosis by RNA in situ hybridization; and the expression in seborrheic keratosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 73 publications
(67 reference statements)
4
41
0
Order By: Relevance
“…p53-regulated carcinoma-associated STAT3-activating long intergenic non-protein coding transcript (PRECSIT) is a recently identified lncRNA with elevated expression in cSCC [129]. PRECSIT is a nuclear-enriched lncRNA downregulated by p53 signaling, and a high level of PRECSIT expression is associated with the absence of functional p53 in cSCC tumor cells in vivo [129].…”
Section: Precsit and Linc00319 Regulate Invasion Of Csccmentioning
confidence: 99%
See 2 more Smart Citations
“…p53-regulated carcinoma-associated STAT3-activating long intergenic non-protein coding transcript (PRECSIT) is a recently identified lncRNA with elevated expression in cSCC [129]. PRECSIT is a nuclear-enriched lncRNA downregulated by p53 signaling, and a high level of PRECSIT expression is associated with the absence of functional p53 in cSCC tumor cells in vivo [129].…”
Section: Precsit and Linc00319 Regulate Invasion Of Csccmentioning
confidence: 99%
“…p53-regulated carcinoma-associated STAT3-activating long intergenic non-protein coding transcript (PRECSIT) is a recently identified lncRNA with elevated expression in cSCC [129]. PRECSIT is a nuclear-enriched lncRNA downregulated by p53 signaling, and a high level of PRECSIT expression is associated with the absence of functional p53 in cSCC tumor cells in vivo [129]. Depletion of PRECSIT inhibits cSCC cell invasion by downregulating STAT3 expression and activation, and production of matrix metalloproteinases (MMPs), MMP-13, MMP-3, MMP-1, and MMP-10 [129], suggesting a tumor-promoting function for PRECSIT (Fig.…”
Section: Precsit and Linc00319 Regulate Invasion Of Csccmentioning
confidence: 99%
See 1 more Smart Citation
“…Bidirectional lncRNAs have transcription start sites at about 1 kb from the promoter region of a protein-coding gene but are transcribed in the opposite direction [ 29 , 121 ]. lncRNAs have tissue-specific expression and are involved in several cell processes by regulating tissue homeostasis, development, repair, or stress response [ 28 ]. Based on their functions, the lncRNAs can be classified into four categories: signal, decoy, guide, and scaffold.…”
Section: Role Of Ncrnas In Csccmentioning
confidence: 99%
“…A growing body of evidence has shown that lncRNAs are involved not only in tissue homeostasis but also in the regulation of tumor initiation, progression, and metastasis with either tumor-promoting or tumor-suppressive functions. Nonetheless, the role of lncRNAs in the cutaneous biology and CSCC tumorigenesis is not yet well known [ 28 , 33 ]. The analysis of the lncRNA landscape reveals their different expression in normal skin and in CSCC samples, in according to the above-mentioned tissues-specific expression of lncRNAs.…”
Section: Role Of Ncrnas In Csccmentioning
confidence: 99%